The evidence for urodynamic investigation of patients with symptoms of urinary incontinence - Rosier, Peter F (Faculty of 1000 Ltd, 2013)
Urodynamic studies are the gold standard to objectively diagnose dysfunction of the lower urinary tract. The widely available evidence for the clinical relevance is, however, fragmented. This article summarizes the published knowledge supporting the use of urodynamic studies in urinary incontinence in female, male and frail patients, as well as patients with relevant neurological disease. Five technological innovations are discussed briefly. Standard urodynamic cystometry can, on the basis of a solid body of evidence, objectively unveil the entire function of the lower urinary tract in all patients with urinary incontinence, regardless of the patients' perception of (ab-)normality of signs and or symptoms.